Renewing the dialogue and the repercussions of the contemporary Iraqi reality (Journal of the College of Basic Education, 2023)
Renewing the Dialogue and the Repercussions of the Contemporary Iraqi-Arab Confrontation:The renewal of dialogue (as a practice, tool, and method in dealing with the other) is one of the most importantThe challenges faced by the Iraqi and Arab intellectual today in the midst of his attempt to play his active and influential roleas a tool for change and cultural movement in Arab and Eastern Mediterranean societies; Where he retreated and missed the dialogueConstruction prevailed the logic of one party at times and political and religious violence at other times » Here we must first standWhen it comes to the meaning of dialogue, and what do we want by (dialogue), which is a comprehensive concept shrouded in a bit of ambiguity, its capacity is overwhelmingAnd helamiteWhat we want by dialogue is the conversation that takes place between two parties on a specific topic and for limited purposesIt ends with a known result that convinces the two parties or is recognized by both parties » Dialogue in itself is a verbal practiceIt is often translated into action and behavior if the negotiating parties are convinced. It includes styleIn dealing with the other, understanding him, allowing him to express his opinion, hearing this opinion, and discussing it, as a result, dialogue isA methodology aimed at transforming difference into a peaceful practice, renouncing violence, and making room for pluralism, contrast, and colouringGiving the other the right to participate and express oneself is therefore an approach to understanding and a method for presenting opinionsAnd dealing with people and things to include all aspects of life.It is no secret to the honorable reader that most of our dialogues today and more than a decade agoIt is of a polemical and polemical nature on all levels, political, social, religious, cultural...etc. SoHere we have summarized the reasons for its absence and decline, and then identified the most prominent means to revive it and provide it with the elements of strengthAnd renewing and resurrecting it in the light of the repercussions of our increasingly complex Arab reality.